COVID-19 Vaccination Leads to Less Pneumonia at Chest CT - Sameer Khairullah MOHAMMED (Modern Medicine)
The study’s objective was to assess, using CT scans, the impact of vaccinations and booster shots on the severity of COVID-19 pneumonia. In this retrospective analysis, 210 Covid-19 patients were included. Within six weeks of receiving a COVID-19 diagnosis, every patient who was included had at least one CT scan and had received a full, partial, or no vaccination. Patients were separated in three groups. A 6-point scale called the Pneumonia Score was used to compare the severity of pneumonia across the three groups. Hypertension, CAD, DM and CKD were the most common comorbidities among all cases. Mean CRP in group I was 94.7±15.63 mg/dl, in group II mean CRP was 96.9±11.44 mg/dl and in group III mean CRP was 97.3±5.35 mg/dl. We found that severity of pneumonia score 5 was higher in group III in 16 (22.8%) as compared to group I in 4 (5.7%) and group II in 8 (11.4%) cases with p value <0.003. Hospital stays and ICU admission was also higher in non-vaccinated case with p value <0.004. Rate of mortality in group I was 7 (10%), in group II was 13 (18.6%) cases while in group III was 15 (21.4%) cases.